Artificial neural network and support vector machine in flood forecasting: A review - Suliman, Azizah; Nazri, Nursyazana; Othman, Marini; Abdul Malek, Marlinda; Ku-Mahamud, Ku Ruhana (2013)
Flood is a natural phenomenon that can cause havocs and deaths.Although flood is sometimes unavoidable, early flood forecasting can be helpful for people to take precaution.In the past decades, researchers have been working on flood forecasting models using artificial intelligence (AI).AI models such as Artificial Neural Network (ANN) and Support Vector Machine (SVM) have been developed and implemented in different locations to help in weather forecasting over the past years. This paper reviews both methods and compares their experimental results.